Block of endothelin-1-induced release of thromboxane A2 from the guinea pig lung and nitric oxide from the rabbit kidney by a selective ETB receptor antagonist, BQ-788. - D'Orléans-Juste, P (1994)
1. The present study characterizes the receptors responsible for endothelin-1-induced release of thromboxane A2 from the guinea pig lung and of endothelium-derived nitric oxide from the rabbit perfused kidney, by the use of the selective ETA receptor antagonist, BQ-123, and a novel selective ETB receptor antagonist, BQ-788. 2. In the guinea pig perfused lung, endothelin-1 (ET-1) (5 nM) induced a marked increase of thromboxane A2 which was reduced by 17 +/- 5.0, 70 +/- 1.0 and 93 +/- 1.2% by BQ-788 infused at concentrations of 1, 5 and 10 nM respectively. In contrast, BQ-123 (0.1 and 1.0 microM) had little or no effect on the ET-1-induced release of thromboxane A2. 3. In the same perfused model, the selective ETB agonist, IRL 1620 (50 nM), stimulated the release of thromboxane A2, but not prostacyclin. The eicosanoid-releasing properties of IRL 1620 were abolished by BQ-788 at 10 nM, yet were unaffected by BQ-123 (1 microM). 4. In the rabbit perfused kidney, BQ-788 (10 nM) potentiated the increase of perfusion pressure induced by endothelin-1 (1, 5 and 10 nM) by approximately 90%, but not that induced by angiotensin II (1 microM). Furthermore, the selective ETB receptor antagonist did not reduce the release of prostacyclin triggered by either peptide. 5. In another series of experiments, pretreatment of the perfused kidney with a nitric oxide synthase inhibitor, L-NAME (100 microM), potentiated the pressor responses to both endothelin-1 and angiotensin II. Under L-NAME treatment, BQ-788 did not further potentiate the pressor response to endothelin-1.(ABSTRACT TRUNCATED AT 250 WORDS)